Mixed mode fracture of a higher order beam model in gradient-dependent plasticity - Salomon, Marie G.; Meftah, Fékri; Marie Reynouard, Jean- (European Journal of Computational Mechanics, 2004)
A higher-order shear-deformable beam model with gradient-dependent plasticity regularisation is presented in this work. The model takes into account a realistic non-linear variation of stresses and strains through the beam thickness. This enables mixed mode fracture analysis. Numerical results are presented for a multilayered beam. The discrete problem size is significantly reduced through this semi-local approach.